Instruments of state risk management of innovative import substitution projects - M. I. Dli; O. V. Bulygina; E. P. Malevich; E. S. Yashin (Путеводитель предпринимателя)
Today, the key priority of state policy is to protect the Russian economy from external threats aimed at reducing the rate of economic growth and scientific and technological development in the country. In these conditions, the primary task facing the state is to overcome dependence on imported supplies of critical goods, components, and raw materials. To quickly solve this problem, it is necessary to intensify innovative activities in the field of import substitution, which, in turn, can be achieved by creating favorable conditions for the implementation of innovative projects to create high–tech products capable of replacing foreign analogues.The subject of the research is the instruments for supporting innovative development in the country in order to ensure economic security. The results consist in the development of a model of the system of state support of innovative activity in order to ensure the economic and technological sovereignty. It is distinguished by the use of the mechanism of public–private partnership for the successful implementation of programs in the field of import substitution of critically important products, components and raw materials. To respond to the risks that may arise during the implementation of such programs, a set of instruments was proposed. They represent a set of measures of state support implementing various options for processing project risks (acceptance, evasion, transfer and distribution).